The regulation of Pre-Messenger RNA splicing - Black, Douglas (Henry Stewart Talks, 2007)
Molecular mechanisms of the basic splicing reaction, Spliceosome assembly, Exon definition, Splicing enhancer and silencer elements, RNA binding proteins that regulate splicing, Protein diversity in metazoan organisms, Tissue specific splicing, Drosophila sex determination pathway, Complex regulation of alternative splicing in mammals
Archived at 2015/07/30